Os tempos do Neolítico na região de Lisboa - Sousa, Ana Catarina (2018)
Approach to the absolute chronologies of the Neolithic in Lisbon region, considering two large units: 1. Neolithic process (Ancient and Middle Neolithic) and 2. The consolidation of peasant societies (Late Neolithic). Dates and contexts of all domestic contexts dates in the Lisbon region are discussed, thus complementing Rui Boaventura’s proposal for the chronology of the Megalithism in the same region.